Tìm x biết :
x-1/ 27= 3/x-1 nhanh nha!!!
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x = 1
b) x = 2
c) ko có Đ/Á
d) x = 3
a) 5 . x3 - 5 = 0
=> 5 . ( x3 - 1 ) = 0
=> x3 - 1 = 0
=> x3 = 1
=> x3 = 13
=> x = 1
b) ( x + 1 )3 = 27
=> ( x +1 )3 = 33
=> x + 1 = 3
=> x = 2
c) Sửa đề :
( x + 1 )4 = 16
=> ( x + 1 )4 = 16
=> ( x + 1 )4 = 24
=> x + 1 = 4
=> x = 2
h) ( 2x - 1 )3 = 125
=> ( 2x - 1 )3 = 53
=> 2x - 1 = 5
=> 2x = 6
=> x = 3
a, \(x^2\) = \(x^3\)
\(x^3\) - \(x^2\) = 0
\(x^2\)( \(x\) -1) = 0
\(\left[{}\begin{matrix}x^2=0\\x-1=0\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)
Vậy \(x\) \(\in\) { 0; 1}
e, 32\(x+1\) = 27
\(3^{2x}\)+1 = 33
2\(x\) + 1 = 3
2\(x\) = 2
\(x\) = 1
g, 62 = 6\(x-3\)
2 = \(x-3\)
\(x\) = 3 + 2
\(x\) = 5
\(a,x^2=x^3\\ \Rightarrow x^2-x^3=0\\ \Rightarrow x^2\left(1-x\right)=0\\ \Rightarrow\left[{}\begin{matrix}x^2=0\\1-x=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)
\(b,3^{2x+1}=27\\ \Rightarrow3^{2x+1}=3^3\\ \Rightarrow2x+1=3\\ \Rightarrow2x=3-1\\ \Rightarrow2x=2\\ \Rightarrow x=2:2\\ \Rightarrow x=1\)
\(c,6^2=6^{x-3}\\ \Rightarrow6^{x-3}=6^2\\ \Rightarrow x-3=2\\ \Rightarrow x=2+3\\ \Rightarrow x=5\)
Có \(\left(x-\dfrac{1}{3}\right)^2\ge0\)
Mà \(\left(x-\dfrac{1}{3}\right)^2=-\dfrac{8}{27}< 0\) \(\Rightarrow\) Vô lý
\(l,\\ 2^x=1=2^0\\ Vậy:x=0\\ m,\\ 3^x=81=3^4\\ Vậy:x=4\\ n,\\ 3^x=37=3^3\\ Vậy:x=3\\ o,\\ 9^x=3^4=\left(3^2\right)^2=9^2\\ Vậy:x=2\)
\(\frac{\left(x-1\right)^3}{-3}\)=\(\frac{-27}{x-1}\)
<=>(x-1)\(^3\).(x-1)=(-3).(-27)
<=>(x-1)\(^4\)=81
<=>(x-1)\(^4\)=3\(^4\)
<=>x-1=3
<=>x=4(Thỏa mãn )
Vậy x=4
Ta có: \(\dfrac{x+1}{29}+\dfrac{x+3}{27}=\dfrac{x-3}{33}+\dfrac{x-7}{37}\)
\(\Leftrightarrow\dfrac{x+30}{29}+\dfrac{x+30}{27}-\dfrac{x+30}{33}-\dfrac{x+30}{37}=0\)
\(\Leftrightarrow x+30=0\)
hay x=-30
`3xx(x-1/6)-2xx(x-1/3)=2/3`
`3x-1/2-2x+2/3=2/3`
`x=2/3-2/3+1/2`
`x=1/2`
`3x(x-1/6)-2x(x-1/3)=2/3`
`3x^2 - 1/2 x- 2x^2 + 2/3x = 2/3`
`x^2+1/6 x =2/3`
`x=(-1 \pm \sqrt97)/12`
=> (x-1).(x-1) = 27 . 3
=> (x-1)^2 = 81
=> x-1=-9 hoặc x-1=9
=> x=-8 hoặc x=10
Vậy x thuộc {-8;10}
Tk mk nha
\(\frac{x-1}{27}=\frac{3}{x-1}\)
=> ( x - 1 ) . ( x - 1 ) = 27 . 3
=> ( x -1 ) . ( x - 1 ) = 81
Vì 9 . 9 = 81
=> x - 1 = 9
=> x = 9 + 1
=> x = 10